Persepsi Siswa terhadap Mata Pelajaran SKI pada Kurikulum Merdeka di MAN 2 Kota Bengkulu - Endang Lestari; Iin Larasati; Lulut Triwuryani; Rini Melati Sukma; Iben Herlanda (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Fun learning can make students like the subject of Islamic Cultural History (SKI). Students' perception of learning Islamic Cultural History (SKI) is a boring subject. The purpose of this study is to describe students' perceptions of Islamic Cultural History (SKI) subjects in the Merdeka curriculum at MAN 2 Bengkulu City. The method used in this study is a quantitative descriptive method. Data collection techniques through observation, questionnaires, and interviews. Data analysis techniques with average tests. The results of this study showed that 21.8% of students did not like the Islamic Cultural History (SKI) lesson due to several factors, namely: 1). Learning methods are less varied, 2). Wide material coverage, 3). Material tends to be memorized. Then 40.6% of students feel uncomfortable in learning Islamic Cultural History which is influenced by: 1). The classroom atmosphere is hot, 2). Classes that are not conducive, 3). Study during the daylight hours.